Ultra‐Fast Portable and Wearable Sensing Design for Continuous and Wide‐Spectrum Molecular Analysis and Diagnostics. Issue 34 (20th October 2022) - Maity, Arnab; Milyutin, Yana; Maidantchik, Vivian Darsa; Pollak, Yael Hershkovitz; Broza, Yoav; Omar, Rawan; Zheng, Youbin; Saliba, Walaa; Huynh, Tan‐Phat; Haick, Hossam
Abstract: The design and characterization of spatiotemporal nano‐/micro‐structural arrangement that enable real‐time and wide‐spectrum molecular analysis is reported and demonestrated in new horizons of biomedical applications, such as wearable‐spectrometry, ultra‐fast and onsite biopsy‐decision‐making for intraoperative surgical oncology, chiral‐drug identification, etc. The spatiotemporal sesning arrangement is achieved by scalable, binder‐free, functionalized hybrid spin‐sensitive (<↑| or <↓|) graphene‐ink printed sensing layers on free‐standing films made of porous, fibrous, and naturally helical cellulose networks in hierarchically stacked geometrical configuration (HSGC). The HSGC operates according to a time‐space‐resolved architecture that modulate the mass‐transfer rate for separation, eluation and detection of each individual compound within a mixture of the like, hereby providing a mass spectrogram. The HSGC could be used for a wide range of applictions, including fast and real‐time spectrogram generator of volatile organic compounds during liquid‐biopsy, without the need of any immunochemistry‐staining and complex power‐hungry cryogenic machines; and wearable spectrometry that provide spectral signature of molecular profiles emiited from skin in the course of various dietry conditions. Abstract : The current article reports on the development of spatiotemporal nano‐/micro‐structural arrangement that enable a wide spectrum of chemicals and complex mixtures to be separated and detected simultaneously when used as wearable‐spectrometry or as ultra‐fast and onsite biopsy‐decision‐making tool for intraoperative surgical oncology. The reported arrangement exhibits rapid discrimination of cancer from healthy tissues as well as spectral signature of volatile organic compounds emanated directly from tumor/skin.